ANALISIS PENGARUH PROMOTION MIX, KUALITAS PELAYANAN TERHADAP CUSTOMERS TRUST MELALUI LOYALITAS PELANGGAN SEBAGAI VARIABEL INTERVENING (STUDI KASUS : MEMBER TUPPERWARE YASMIN PEMALANG) - Handayani, Tri; Nihayah, Anini; Murdianingsih, Dian; Rosyadi, Noor (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2023)
The purpose of this study was to analyze the effect of promotion mix and service quality on customers' trust through customer loyalty. The object of research in this case is Tupperware customers in Pemalang Regency who buy Tupperware products with a minimum of two purchases, and the segmentation is buyers aged over 17 years. Purposive sampling technique was used in this study. There are 100 respondents who comply with the minimum sample size rule on the fourth construct variable. The data analysis technique used in this case is the Structural Equation Model (SEM) from the AMOS 21 software. The model proposed in this research case can be accepted after meeting the assumptions of normality and Standardized Residual Covariance ± 2.58 and the Determinant Sample Covariance value with a matrix result of 5,597. The results of the SEM analysis to meet the criteria for the Goodness of Fit - Full Model model are chi square = 258,691; probability = 0.000; GFI = 0.775; AGFI = 0.709; TLI = 0.931; CFI = 0.941. The results of this model can be used in the case of this study. Based on the results of the study, it can be concluded that the promotion mix and service quality can increase customer trust and customer loyalty. In addition, customer trust can increase customer loyalty. Meanwhile, customer loyalty can affect customer trust.